Studies in Christian ethics. - Society for the Study of Christian Ethics (London Sage Publications, 1988)
"Contents of each year's volume are related to the subject of the conference of the Society for the Study of Christian Ethics, under whose patronage the journal begins its life."--Editorial, v. 1, no. 1 (1988).
Each issue contains specific theme.
UP System perpetual contents: 2019
Keywords: Christian ethics -- Periodicals